2010
DOI: 10.1016/j.jhazmat.2009.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of humic acids during composting of activated sludge-green waste: Elemental analysis, FTIR and 13C NMR

Abstract: The humic acids extracted from a compost of activated sludge at different stages of maturity were characterized by various chemical techniques. Elemental analysis showed the reduction of H, and the H/C and C/N ratios and an increase in the proportion of N and S. At the end of composting C% and O% presented the same values as initially, although they increased in the intermediate stage. Based on the ratios of FTIR absorbance it was shown that the end product was enriched in etherified and peptidic compounds abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
117
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(132 citation statements)
references
References 35 publications
(55 reference statements)
13
117
0
2
Order By: Relevance
“…In addition, T1, T1+T2 and T1+T3 containing B. licheniformis (strain 1), resulted in relatively lower amounts of aromatic C (1637 cm -1 ), indicating that this strain might have a relative strong degradation capacity for aromatic C. The absorption peak area at 3340 cm -1 changed less between various treatments and before degradation by comparison, it was due to high levels of hydroxyl groups in the extraction solution. Amir et al (2010) reported that the amount of polysaccharides in HA displayed a relative increase after microbial composting, and this research reached the same higher levels of MBC were detected in T1, T3 and T1+T3 compared with the other treatments (Table 2). In terms of the C degradation rates in the various treatments it ranged from 18.91% to 52.05%, with the highest in T2+T3 and the lowest in T2.…”
Section: Figure 2 Carbon Respiration (Cr) Dynamics Of Different Treasupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, T1, T1+T2 and T1+T3 containing B. licheniformis (strain 1), resulted in relatively lower amounts of aromatic C (1637 cm -1 ), indicating that this strain might have a relative strong degradation capacity for aromatic C. The absorption peak area at 3340 cm -1 changed less between various treatments and before degradation by comparison, it was due to high levels of hydroxyl groups in the extraction solution. Amir et al (2010) reported that the amount of polysaccharides in HA displayed a relative increase after microbial composting, and this research reached the same higher levels of MBC were detected in T1, T3 and T1+T3 compared with the other treatments (Table 2). In terms of the C degradation rates in the various treatments it ranged from 18.91% to 52.05%, with the highest in T2+T3 and the lowest in T2.…”
Section: Figure 2 Carbon Respiration (Cr) Dynamics Of Different Treasupporting
confidence: 71%
“…The presence of certain functional groups and their relative contents in HA can be determined based on the position and peak intensity of the absorption peak. The assignment of the IR spectra of HA was performed according to the literature (Amir et al, 2010). The IR spectral analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the blank culture media (sea salt only), seven absorption bands were observed for the recycled media sample in the regions of 3352, 2343, 2260, 1639, 1425, 1384 and 1139 cm −1 . A strong broad stretched peak ranging from 3600 to 3200 cm −1 with maximum of 3352 cm −1 corresponded to a hydroxyl group [41][42], implying the presence of a polysaccharide substance in the recycled media. Two weak peaks at 2343 and 2260 cm −1 were either due to CO 2 adsorption or from an amine group [43].…”
Section: Growth Inhibitors Identificationmentioning
confidence: 99%
“…The peak observed at 1639 cm −1 may correspond to the ring-stretching of mannose or galactose [44], or to the aromatic \ \C_C\ \ groups of the humic substances [42,45]. The two peaks observed at 1425 and 1384 cm −1 could have been caused by the\ \OH group of phenol, symmetrical stretching of the\ \COO group of humic substances [42,46], or to the \ \CH 2 \ \ bending of saccharides [47][48][49][50], whereas the peak at 1139 cm − 1 may have been caused by either the C\ \O\ \C and C\ \O groups of carbohydrates [44,51] or the aliphatic structures of humic substances with high levels of oxygen-rich functional groups [45]. Adsorption peaks ranging from 1000 to 800 cm − 1 were attributed to pyranoidal ring structure vibration of saccharides [49][50], and the adsorption peak at 644 cm − 1 corresponded to the stretching of alkyl-halides [51].…”
Section: Growth Inhibitors Identificationmentioning
confidence: 99%
“…All samples exhibited bands of very low intensity at wave numbers below 900 cm , attributed to C-O stretching and OH bending of the lactonic, ether and phenol groups, was found in samples ASBL and ALB with greater intensity than in the other two materials (Dantas et al 2011). A peak at 1420 cm , attributed to the C = O bond of carboxylic groups (Amir et al 2010). All spectra showed a strong wide absorption band at 3600-3200 cm −1 with a maximum at approximately 3420 cm −1 due to surface hydroxyl groups and chemisorbed water.…”
Section: Resultsmentioning
confidence: 92%